Perceptions of Organizational Politics: A Need Satisfaction Paradigm - Rosen, Christopher C.; Ferris, D. Lance; Brown, Douglas J.; Chen, Yuanyi; Yan, Ming (Organization Science, 2014)
Stressor and exchange relationship paradigms have developed in isolation from each other to explain the negative effects of perceived organizational politics. We outline how these different paradigms share a common basis—a focus on psychological need satisfaction—and develop a needs-based paradigm to account for the negative effects of perceived organizational politics. Moreover, we argue that psychological need satisfaction acts as an unmeasured third variable, which, once accounted for, should limit the utility of stressor and exchange relationship paradigms. Across four samples using a combination of multiple sources, operationalizations of constructs, and measurement occasions, we found full support for the needs-based paradigm as a mediator of the effects of politics on contextual performance, creativity, and proactive behavior, whereas strain and exchange relationship constructs by and large had no effect on outcomes once psychological need satisfaction was accounted for. Theoretical implications and future research directions are discussed.